The Analysis of Factors Affecting Stage Level of Breast Cancer Patients at RSUD DR. SOETOMO Surabaya - Susilaningrum, Destri; Azizah, Nur; Salamah, Mutiah; Ratna D, Mukti (Green Publisher, 2022)
Breast cancer is the cancer with the largest number in the world, and ranks as the fifth largest cause of death, which is 6.9% of the total 9,958,133 million cases of cancer deaths. Breast cancer is one of the main killers of women in the world and in Indonesia. Breast and cervical cancer dominate cancer cases in East Java. Throughout 2019, RSUD Dr. Soetomo Surabaya received 167,000 cancer patients, and the highest case was breast cancer. The high number of breast cancer sufferers makes this disease requires special attention. The cancer staging or staging system is based on whether the cancer has spread from the breast to other parts of the body. Cancer stage is divided into two categories, namely early stage (stages 0 to III A) and late stage (stages III B to IV). This study will examine the factors that affect the level of cancer stage in breast cancer patients at RSUD Dr. Soetomo Surabaya in 2019. Using the binary logistic regression analysis method, it was found that the factors that significantly influence the stage of breast cancer are Grade and Obesity with a classification correctness level of 82.5%.